Studi Perencanaan Penerangan Jalan Umum Panel Surya di Kelurahan Gading Kasri Kecamatan Klojen - Asfari Hariz Santoso; Ahmad Hermawan; Muhammad Azzam Wian Panantuan (Elposys: Jurnal Sistem Kelistrikan, 2021)
Malang City is a city that has an increasing need for electrical energy in the technological era, which today is very much needed in fulfilling daily life, both for household, social and industrial needs. One of them is the supply of electrical energy for Public Street Lighting (PJU). If you only rely on the supply of electrical energy from grid, this is a heavy burden that must be borne by the Malang City Regional Budget to pay the electric energy consumption bill for the PJU. This study aims to determine the comparison of the use of conventional PJU with solar powered PJU (PJUTS) in the area of Gading Kasri Village, Klojen District, Malang City both in terms of technical installations which include solar panels, batteries, and charger controllers as well as from an economic point of view. That shines for 5 hours every day, the solar panel power specifications are 240 Wp with 37 points of light. Budget calculations using the ACS (Annual cost system) which is obtained in the 16th year the difference from the initial investment costs and revenue from sales met at BEP (break event point) amounting to Rp. 256,761,376.00.